Harvey Warren Zorbaugh (1896-1965) (Revista de sociología clínica, 2023)
Harvey Warren Zorbaugh was born in East Cleveland, Ohio (US) on September 20, 1896. He received a BA degree from Vanderbilt University and a PhD in sociology from the University of Chicago. Starting in the mid-1920s, sociologists directed or were centrally involved in clinics in several US cities. In Chicago, Zorbaugh was one of the directors of the Lower North Child Guidance Clinic.